Spiraea fangii (Rosaceae), a new species from Sichuan, China - Hu, Hao-Yu; Tan, Jin-Bo; Xie, Deng-Feng; Zhang, Jian; He, Xing-Jin (Phytotaxa, 2016)
Spiraea fangii (Rosaceae) is described and illustrated from Sichuan Province, China. The difference on habitat and morphology characters between S. fangii and morphologically related species S. myrtilloides are presented.